1982
DOI: 10.1093/infdis/146.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Antibody to Cytomegalovirus Early Antigen in Vaccinated, Normal Volunteers and Renal Transplant Candidates

Abstract: Antibody to cytomegalovirus early antigen (CMV-EA) has been demonstrated in acute CMV infection. Other investigators have suggested that antibody to CMV-EA would distinguish acute CMV infection from past infection and could therefore be diagnostically useful. Antibody to CMV-EA has been demonstrated in reactivated CMV infection, in infants with congenital infection, and in pregnant women. Antibody to CMV-EA was studied in renal transplant candidates receiving Towne strain CMV vaccine, healthy adults receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The presence of high levels of anti-CMV-EA antibodies may be a reflection of active virus replication in the host as indicated in previous studies (10,23,28,32) and in studies on vaccination with attenuated CMV (9).…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…The presence of high levels of anti-CMV-EA antibodies may be a reflection of active virus replication in the host as indicated in previous studies (10,23,28,32) and in studies on vaccination with attenuated CMV (9).…”
mentioning
confidence: 61%
“…Our present data failed to show a distinct relationship between the level of anti-CMV-EA antibodies and virus excretion. Additionally, antibodies against CMV-EA were frequently detectable in normal CMV-seropositive individuals (9,28).…”
Section: Resultsmentioning
confidence: 99%
“…IgG determination, sera were tested using a nuclear antigen obtained by glycine extraction of infected and uninfected nuclei prepared as described (Friedman et al, 1982).…”
Section: Determination Of Anti-hcmv Igg and Igm Antibody By Elisa Formentioning
confidence: 99%
“…Results of some studies have indicated that antibody responses to the early antigens of Epstein-Barr virus and human cytomegalovirus are of short duration, and that the presence of antibodies to these antigens is suggestive of active infections with the viruses Henle et al, 1971;The et al, 19741. However, more recent studies have cast doubt upon the diagnostic significance that can be attached to the presence of antibodies to early antigens of these viruses, since such antibodies have been demonstrated in individuals without evidence of active viral infections [Farber et al, 1979;Favart et al, 1978;Friedman et al, 1982;Gerna et al, 1979;Gotlieb-Stematsky et al, 1978;Griffiths et al, 1980;Kurstak et al, 19781. One study has been reported in which antibodies to early antigens of varicella-zoster virus (VZV) were demonstrable only in varicella or herpes zoster infections, and were considered to be markers of current VZV infection [Gerna et al, 19791.…”
Section: Introouctionmentioning
confidence: 99%
“…Results of some studies have indicated that antibody responses to the early antigens of Epstein-Barr virus and human cytomegalovirus are of short duration, and that the presence of antibodies to these antigens is suggestive of active infections with the viruses Henle et al, 1971;The et al, 19741. However, more recent studies have cast doubt upon the diagnostic significance that can be attached to the presence of antibodies to early antigens of these viruses, since such antibodies have been demonstrated in individuals without evidence of active viral infections [Farber et al, 1979;Favart et al, 1978;Friedman et al, 1982;Gerna et al, 1979;Gotlieb-Stematsky et al, 1978;Griffiths et al, 1980;Kurstak et al, 19781. One study has been reported in which antibodies to early antigens of varicella-zoster virus (VZV) were demonstrable only in varicella or herpes zoster infections, and were considered to be markers of current VZV infection [Gerna et al, 19791. The present investigation on antibody responses to early antigens of VZV and herpes simplex virus (HSV) was undertaken with the following aims: (1) to explore further antibody responses to early antigens of VZV and HSV in primary, reactivated, and latent infections in efforts to determine the diagnostic significance that should be attached to these antibody responses, (2) to determine whether the serodifferentiation of VZV and HSV infections might be improved through the use of early antigen preparations, (3) to determine whether early antigens produced with different blocking agents might differ in their serological reactivity, and (4) to study the reactivity of class-specific viral antibodies with early antigens of VZV and HSV.…”
Section: Introouctionmentioning
confidence: 99%